Oribatid mites (Acari, Oribatida) of yew, cypress and pine litter in southern Italy - Seniczak, Stanisław; Seniczak, Anna (Biological Letters, 2013)
Oribatid mite communities were investigated in southern Italy in litter under yew, pine and cypress trees. These mites achieved the highest density in yew and cypress litter in a park in the inland town of Caserta, and the lowest density in pine litter at the coast of Capo Vaticano. In these mite communities, only 1-4 species were abundant, so the Shannon index H’ was rather low. The density of oribatid mites, species number, and dominance structure depended greatly on the kind of litter. The most abundant and common was Zygoribatula propinqua, but the highest density in yew litter was achieved by Oribatella superbula. In oribatid mite communities, the juveniles usually dominated, but the age structure of species greatly depended on the kind of litter.